The Effect of Applying Cubes Story As a Teaching Media on The Students' Writing Skill Improvement in English Narrative Text - Nafa Nazwa Purba; Farida Repelita Waty Kembaren; Ahmad Amin Dalimunthe (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The background of this research is that there are difficulties in writing narrative texts in high school students in English subjects. This study aims to measure whether there is any significant effect of applying cubes story on students' writing ability in English narrative text. The study employed a quantitative approach with a quasi-experimental design. The research samples were divided into two classes, namely the experimental class and the control class. The experimental class received treatment from the researcher using a cube story while the control class did not receive any treatment other than what the teacher usually used. The population of this research is all of the 11th-grade students of MAN 1 Deli Serdang In academic 2023/2024. The sample of this research was two classes of 11th grade of MAN 1 Deli Serdang, XI A MIPA for the experiment class and XI B MIPA for the control class. Writing tests were used as a research instrument to collect data. The tests were pre-tests which were given before the treatment and post-tests were given after the treatment. To analyze the data, the researcher used IBM SPSS version 25. The result of this research post-test t-test resulted in a lower p-value (2-tailed significance) than the significance level (α) (0.000 < 0.05). Furthermore, the t-value is higher than the t-table, 5.856 > 1.677. It stated that the null hypothesis (h0) was rejected while the alternative hypothesis (ha) was accepted. The data indicate the effect size of a result is 1.67. It signifies that the impact falls into the strong category. The conclusion is that story cubes have a strong effect on students' writing in narrative text, particularly in the eleventh grade of MAN 1 Deli Serdang In academic 2023/2024.